2019
DOI: 10.37897/rmj.2019.4.13
|View full text |Cite
|
Sign up to set email alerts
|

Infecţia cu Clostridium difficile după tratamentul pancreatitei acute

Abstract: REzumatInfecţia cu Clostridium difficile a devenit frecvent asociată cu îngrijirile medico-chirurgicale în ultimii ani. Managementul defectuos al antibioterapiei profilactice a pancreatitei acute, în ciuda protocolizării tratamentului, a dus la lărgirea spectrului de rezistenţă la antibiotice. Acesta este un studiu retrospectiv incluzând 19 pacienţi diagnosticaţi cu infecţie cu C. difficile după tratamentul pancreatitei acute internaţi în clinica de Chirurgie Generală a Spitalului Clinic de Urgenţă București î… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Intestinal Clostridiaceae are subdivided into 19 clusters with 120 species, and their growth is suppressed by other anaerobes in a healthy gut [ 73 ]. When alterations of the microbiota and the intestinal microenvironment occur, for example, following treatments with antibiotics, proton pump inhibitors, and chemotherapy or when there are associated comorbidities (inflammatory bowel disease, diabetes mellitus, cancer, and pancreatitis) or recent hospitalizations, this creates the premises for C. difficile expansion and subsequent infection [ 74 , 75 ]. Therefore, it was shown that for the elderly, where the infection with C. difficile is nonresponsive to treatment with metronidazole or vancomycin and is lethal in 15% of cases, the most beneficial intervention is the correction of the microbiota through fecal transplantation [ 76 ].…”
Section: Diarrheal Illnessesmentioning
confidence: 99%
“…Intestinal Clostridiaceae are subdivided into 19 clusters with 120 species, and their growth is suppressed by other anaerobes in a healthy gut [ 73 ]. When alterations of the microbiota and the intestinal microenvironment occur, for example, following treatments with antibiotics, proton pump inhibitors, and chemotherapy or when there are associated comorbidities (inflammatory bowel disease, diabetes mellitus, cancer, and pancreatitis) or recent hospitalizations, this creates the premises for C. difficile expansion and subsequent infection [ 74 , 75 ]. Therefore, it was shown that for the elderly, where the infection with C. difficile is nonresponsive to treatment with metronidazole or vancomycin and is lethal in 15% of cases, the most beneficial intervention is the correction of the microbiota through fecal transplantation [ 76 ].…”
Section: Diarrheal Illnessesmentioning
confidence: 99%